PARP Inhibitors in the Management of Ovarian Cancer: ASCO Guideline. Issue 12 (December 2020) - Tew, William P.; Lacchetti, Christina; Ellis, Annie; Maxian, Kathleen; Banerjee, Susana; Bookman, Michael; Jones, Monica Brown; Lee, Jung-Min; Lheureux, Stéphanie; Liu, Joyce F.; Moore, Kathleen N.; Muller, Carolyn; et al.
Abstract : (Abstracted from J Clin Oncol 2020;38:3468–3493) Despite advances in diagnosis and therapy, an individual with ovaries carries an approximate 1 in 108 lifetime chance to die due to ovarian cancer (OC). Primary therapy typically involves surgical cytoreduction and a combination regimen of platinum and a taxane.